Strategi Inovatif Pembelajaran FPB dan KPK dengan Menggunakan Media Congklak untuk Meningkatkan Hasil Belajar Matematika pada Siswa Kelas IV SD - Amanda Nurul Putri Rambe; Cindy Aulia Br Ginting; Indah Novita; Winata Syahputra Saragih; Elvi Mailani; Nur Rarastika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Learning the concepts of Greatest Common Factor (GCF) and Least Common Multiple (LCM) at the elementary school level faces significant challenges due to their abstract and complex nature. This study aims to develop and evaluate the effectiveness of innovative learning strategies using the congklak game in enhancing students' understanding of GCF and LCM concepts. The research employed a Research and Development (R&D) methodology with the ADDIE model, involving 14 fifth-grade students from SDS Nahdlatul Ulama Medan as research subjects. The congklak game was developed as an interactive learning tool that integrates traditional game elements with mathematical concepts. Implementation was conducted through structured phases including needs analysis, media design, prototype development, learning implementation, and outcome evaluation. Research findings demonstrate significant improvements in students' conceptual understanding and learning outcomes. The use of congklak media successfully created contextual learning experiences that enabled students to visualize abstract GCF and LCM concepts through manipulation of congklak seeds. This strategy also increased active student engagement, promoted collaborative learning, and created an enjoyable learning atmosphere. Data analysis showed improved average student scores and higher learning mastery rates compared to conventional teaching methods. This study provides practical contributions to the development of mathematics teaching strategies at the elementary school level, particularly in teaching GCF and LCM concepts. The research findings recommend the use of congklak media as an effective alternative for enhancing the quality of meaningful mathematics learning oriented toward conceptual understanding.